Use of synchronously excited fluorescence to assess the accumulation of membrane potential probes in yeast cells - Plásek, J; Gásková, D; Vecer, J; Sigler, K (Folia microbiologica, 2000)
Evaluation of emission spectra of fluorescent probes used for the monitoring of membrane potential in microbial cells can be greatly facilitated by using synchronously excited spectroscopy (SES). This method permits the suppression of undesirable spectrum components (contributions due to scattered light or cell autofluorescence) and leads to considerable increase in monitored emission intensity and to narrowing of spectral peaks. It allows an efficient fractional decomposition of the probe fluorescence spectra into their free and bound dye fluorescence components. The usefulness of the method was tested by monitoring the accumulation of the fluorescent membrane potential probe diS-C3(3) in yeast cells, which serves as a qualitative measure of the membrane potential.
Keywords: Saccharomyces cerevisiae; fluorescenční barviva; membránové potenciály; Carbocyanines; Membrane Potentials; Fluorescent Dyes; Spectrometry, Fluorescence; karbocyaniny; fluorescenční spektrometrie